Tetramethyl ammonium chloride as dual functional inhibitor for methane and carbon dioxide hydrates - Khan, M.S. (2019)
This experimental work evaluates the dual functional (thermodynamic and kinetic) behaviour of quaternary ammonium salt namely tetramethyl ammonium chloride (TMACl) for both methane (CH4) and carbon dioxide (CO2) hydrates. The Hydrate Liquid Vapour Equilibrium (HLwVE) data for CH4 and CO2 are evaluated in the presence and absence of aqueous TMACl solutions (1, 5 and 10 wt) through T-cycle method at different temperature and pressure conditions. The inhibition impact, i.e., average suppression temperature (ÎÅ¦) and Hydrate dissociation enthalpies (ÎHdiss) are also reported for the considered systems for both gases. The study is further extended to evaluate the formation kinetics of CH4 and CO2 hydrated in the presence and absence of aqueous TMACl systems. The impact of TMACl is reported via the induction time, the initial formation rate and a gas uptake at different subcooling temperatures for both gases. Furthermore, the kinetic inhibition performance of TMACl is also assessed via the relative inhibition performance (RIP) compared with literature systems for both CH4 and CO2 hydrates. Additionally, an electrolyte based thermodynamic model proposed by Dickens and Quinby-Hunt, (1997) is applied to predict the HLwVE temperatures of both gases (CH4 and CO2) in the presence of TMACl. The obtained thermodynamic and kinetic results indicate that TMACl efficiently acts as a potential dual functional hydrate inhibitor for CH4 and CO2 gases. Therefore, the outcome of its efficacy, this study will envision the use of TMACl for both CH4 and CO2 hydrate systems and can potentially be applied in offshore flow assurance strategies. Â© 2018 Elsevier Ltd